Doing justice [compact disc, unabridged] : a prosecutor's thoughts on crime, punishment, and the rule of law - Bharara, Preet, 1968- (Random House Audio, 2019)
A former federal prosecutor for the Southern District of New York presents an overview of the American justice system, drawing on case histories and personal experiences to discuss why the rule of law is essential to U.S. society.